AB0152 Low avidity anti-citrullinated protein antibodies (ACPA) are associated with enhanced radiological progression in rheumatoid arthritis. (23rd January 2014) - Willemze, A.; Suwannalai, P.; Britsemmer, K.; Knevel, R.; Scherer, H.; Levarht, E.; van der Helm-van Mil, A.; van Schaardenburg, D.; Huizinga, T.; Toes, R.; Trouw, L.
Abstract : Objectives: Anti-citrullinated protein antibodies (ACPA) are specific for Rheumatoid Arthritis (RA) and have been implicated in disease pathogenesis. Previously we have shown that ACPA display a considerably lower avidity as compared to antibodies against recall antigens. Nonetheless, ACPA-avidity did vary between patients. As antibody-mediated effects are influenced by antibody-avidity, we now investigated ACPA-avidity in relation to biological activity and clinical outcome. Methods: We determined the avidity of ACPA and related this with severity of joint damage in two Dutch early-RA cohorts containing 199 and 132 patients respectively. Differences in effector functions of low and high avidity ACPA were studied. Results: Extensive variation in ACPA avidity between patients was observed. This allowed the analysis of the relationship between avidity and severity. The presence of low avidity ACPA is associated with a higher rate of joint destruction. This finding was replicated in an independent cohort. Analysis of the properties of low-versus high avidity ACPA revealed that low avidity ACPA are less hampered in their ability to bind "new" citrullinated antigens. Although no differences could be observed regarding cellular activation via Fc-gamma receptors, low avidity ACPA were more potent in activating the complement system. Conclusions: Patients with low avidity ACPA display a higher rate of joint destruction. Low avidity ACPA display a higher potency to interact with more citrullinated antigens in time and show that low avidity ACPA are more potent in complement activation. These data indicate that (low) avidity impacts on the biological activity of ACPA and associates with worse radiological outcome. Disclosure of Interest: None Declared